DEEP FLUIDS IN SUBDUCTION ZONES - Scambelluri M.; Philippot P. (My University, 2001)
The fluid inclusions preserved in high and ultrahigh pressure rocks provide direct information on the compositions of fluid phases evolved during subduction zone metamorphism, and on fluid–rock interactions occurring in such deep environments. Recent experiments and petrologic studies of eclogite–facies rocks demonstrate that stability of a number of hydrous phases in all rock systems allows fluid transport into the mantle sources of arc magmas, as well as into much deeper levels of the Earth's mantle. In eclogite–facies rocks, the presence of large ion lithophile elements (LILE) and light rare earths (LREE)-bearing hydrous phases such as epidote and lawsonite, together with HFSE repositories as rutile and other Ti-rich minerals, controls the trace element budget of evolved fluids and fluid-mediated cycling of slab components into the overlying mantle.